Intraductal papillary mucinous neoplasm in a 26 year old lady: a diagnostic therapeutic challenge! - Jadhav, Sarojini; Ali, Faiyaz; Kadam, Shubhangi; Chopra, Ashok Kumar; Iyer, Vishakha Sheshadri (International Surgery Journal, 2022)
Intraductal papillary mucinous neoplasm of the pancreas is a mucin producing cystic mass which originates from the pancreatic duct first defined by Ohashi et al in 1982. World Health Organization (WHO) classified mucin-producing cystic neoplasms of pancreas into 2 groups: mucinous cystic neoplasm and IPMNs. IPMN is a difficult diagnosis. Many patients may be asymptomatic for as long as 1 year and few show vague symptoms. Due to advances in radiology the incidental detection of IMPNs have increased. A 26 years old lady presented with vague pain in abdomen since 1 month with an incidental USG (A+P) finding of a cystic avascular lesion between the head and body of pancreas. CECT (A+P) and MRCP confirmed the diagnosis of branched duct IPMN with worrisome (cyst size >3 cm). Suggestive of branched duct IPMN with worrisome (cyst size >3 cm) considering the age of the patient, size of the cyst and worrisome features patient was posted for excision cyst. The tumour was well circumscribed arising from branched duct with communication with the main duct. Tumour was resected well. Histopathology revealed a benign cystic neoplasm of pancreas s/o IPMN with no e/o malignancy. In younger age group it is better to resect the tumour than timely surveillance as longer life expectancy in them provides an adequate time span for a low grade, branched duct tumour with worrisome features to undergo malignant transformation.